An Assessment of Housing Quality in Uttar Pradesh: Spatial Inequality - Ahmed, Naushaba Naseem (National Geographical Journal of India, 2022)
Housing is universally considered as the second most essential human need after food and one of the major economic assets in every nation. Housing crisis and the deterioration in the quality of housing infrastructure as well are serious issues that need to be addressed on the top priority. This paper attempts to construct the Housing Quality Index (HQI) using Principal Component Analysis (PCA) by assigning weightage to each variable using Census household data 2011. For the construction of HQI, three sub-indices are calculated namely, Housing Structure Index, Housing Service Index and Proxy Wealth Index incorporating 19 indicators. The selected indicators are normalized by UNDP standardization method leading to calculated values that ranges between 0 (the highest value) and 1 (the lowest value). Further, the regression analysis is applied to highlight the causal relationship between the Housing Quality Index and the each individual quality indices viz., housing structure, housing services and proxy wealth assets. The result shows that Gautam Buddha Nagar (0.123) has occupied the first position in term of housing quality followed by Ghaziabad (0.207) and Lucknow (0.270) while on the other end, Shravasti district (1.126) is the least developed followed by Bahraich (1.109) and Chitrakoot (1.104). Finally, it is recommended that the government`s efforts at the state level be directed towards making available minimal standard of housing for the backward areas dominated by poor